Online Gaming and Social Behavior Among Adolescents: Evidence from Mobile Legends Players in Junior High School - Sri Ira Suharwati; Itaanis Tianah; Ach Sihabuddin (Universtias Islam Negeri Madura, 2026)
Mobile Legends is a game that is widely popular among all demographics, particularly teenagers, and can lead to dependency or addiction. The impact of this online game also affects children’s academic performance and behavior, potentially leading to social deviance. The purpose of this study is to analyze the influence of Mobile Legends on students’ social attitudes. This study is an ex post facto study. The target population consists of all students at SMP Islam Nurul Iman. The sampling technique used was saturation sampling. Data collection methods included observation, questionnaires, and documentation. Data analysis employed simple linear regression using SPSS software. The results revealed a correlation coefficient (R) of 0.429 with an R-squared value (coefficient of determination) of 0.184, indicating that Mobile Legends has an influence on students’ social attitudes. Changes in social behavior include rarely socializing with peers, becoming easily emotional toward the surrounding environment, reduced interaction with parents, and decreased study time. Efforts to prevent these impacts can be undertaken by parents, teachers, and the adolescents themselves. These include managing playtime and parental guidance in technology use